A Turkish case of congenital chloride diarrhea with SLC26A3 gene (c.2025_2026insATC) mutation: Diagnostic pitfalls - Ferda ÖZBAY HOŞNUT; Eda KARADAĞ ÖNCEL; Mehmet Yekta ÖNCEL; Figen ÖZÇAY (Turkish Journal of Gastroenterology, 2019)
-